Membuat Aplikasi Mobile Tanpa Coding menggunakan AppSheet - Auliya Rahman Isnain; Heni Sulistiani; Dedi Darwis; Ikbal Yasin (Journal of Engineering and Information Technology for Community Service, 2023)
Mobile apps themselves are developed by human resources who master the IT field, in which there is a programming system as the main component in developing an application. Based on the results of the questionnaires that were distributed before and after the activity, at the time before the activity as many as 50 students did not understand about making mobile applications without coding using an appsheet. After training and filling out questionnaires after the presentation of the material there was a significant increase in making mobile applications without coding using an appsheet, namely 57 students understood the material provided and were able to make mobile applications without coding using an appsheet.